Resin-based self-lubricating friction material, preparation method and brake pad
By using resin-based self-lubricating friction materials, the problems of poor aging resistance and high noise in wind power yaw systems are solved, and efficient and low-noise friction performance is achieved, extending service life and reducing operation and maintenance costs.
Patent Information
- Application Number
- CN202510018941.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
The existing friction materials have problems such as poor aging resistance, high friction noise, high wear rate, and easy to cause brake disc damage in wind power yaw systems, which affect the safety and operational efficiency of wind power units.
Resin-based self-lubricating friction materials are prepared by hot-pressing molding and heat treatment processes to form high-performance friction materials.
The stability, lubrication stability and wear resistance of the friction coefficient are achieved, the noise during yaw braking is reduced, the service life of the friction materials is extended, and the operation and maintenance costs of wind power generation is reduced.
Smart Images

Figure CN119823524A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of braking, and in particular to a resin-based self-lubricating friction material, a preparation method and a brake pad. Background Art
[0002] Wind energy resources are one of the most promising renewable energy sources for large-scale development and utilization; wind energy used for power generation (referred to as "wind power") is an inexhaustible renewable energy source, and its research and development has developed rapidly; horizontal-axis wind turbines are equipment that utilize wind energy. Because of their unique design advantages, they have stood out from the competition among various new energy technologies and have become one of the most watched new energy industries in the world. For example, the power of Dongfang Electric's wind turbines can reach 18MW.
[0003] The yaw system is one of the components of a horizontal axis wind turbine. Its function is to quickly and smoothly align the wind direction when the direction of the wind speed vector changes, so that the wind rotor can obtain the maximum wind energy. The yaw brake is a key component of the wind power yaw system, and the core brake component of the yaw brake is the friction material. The quality of the friction material will seriously affect the safety, work efficiency and operating power generation cost of the wind turbine. The friction material is required to have high mechanical properties, stable friction coefficient, wear resistance, low noise, and high-performance environmental protection technical indicators without damaging the disc. These indicators are important technical guarantees for the safe and stable operation of wind power.
[0004] Yaw drag friction vibration noise, severe scratches on the yaw drag friction material pair, yaw self-excited vibration alarm shutdown and main cabin yaw instability and other equipment operation failures have long affected the normal operation of wind turbine yaw brakes for many years. At present, friction materials contain rubber and metal fiber raw materials. Rubber has poor aging resistance, and metal fibers are prone to agglomeration and hardening points due to repeated friction during the yaw process. These will cause the damping brake material to be worn and strained due to long-term use, causing sharp yaw noise and wind turbine tower impact vibration alarm failure; these failures seriously affect the normal power generation of wind turbines and the living environment of surrounding residents. In order to reduce the operating cost of wind power, it is particularly important to develop a yaw drag friction engineering material that can be suitable for the normal operation of wind turbines after the overall structure of the wind turbine is determined, so as to reduce noise, frequent impact vibration failures and other yaw failures, as well as resin-based self-lubricating friction materials that do not damage the pair. Summary of the invention
[0005] The purpose of the present invention is to provide a friction material, method, brake pad and application in view of the problems existing in the friction material in the prior art.
[0006] In order to solve the technical problem of the present invention, the technical solution adopted by the present invention is:
[0007] The resin-based self-lubricating friction material comprises the following components by weight percentage:
[0008] Thermoplastic phenolic resin 10-30%;
[0009] Teflon 10-15%;
[0010] Polyethylene fiber 6-12%;
[0011] Mineral fiber MF02-2 5-10%;
[0012] Aramid pulp 5-10%;
[0013] Antimony sulfide 4-15%;
[0014] Alumina 10-15%;
[0015] Brass powder Zn20 5~15%;
[0016] Talc 5-15%.
[0017] Furthermore, the friction material comprises the following components by weight percentage:
[0018] Thermoplastic phenolic resin 18%;
[0019] Teflon 10%;
[0020] Polyethylene fiber 11%;
[0021] Mineral fiber MF02-2 10%;
[0022] Aramid pulp 9%;
[0023] Antimony sulfide 13%;
[0024] Alumina 13%;
[0025] Brass powder Zn20 6%;
[0026] Talc 10%.
[0027] Furthermore, the mesh number of thermoplastic phenolic resin is 200-400 mesh, the mesh number of Teflon is 40-200 mesh, the length of polyethylene fiber is 3-6 mm, the aspect ratio of mineral fiber MF02-2 is 8:1-18:1, the length of aramid pulp fiber is 0.9-1.35 mm, the mesh number of antimony sulfide is 200-320 mesh, the mesh number of alumina is 500-600 mesh, the mesh number of brass powder Zn20 is 150-200 mesh, and the mesh number of talc is 600-800 mesh.
[0028] Furthermore, the mesh number of thermoplastic phenolic resin is 300 mesh, the mesh number of Teflon is 100 mesh, the length of polyethylene fiber is 3 to 6 mm, the aspect ratio of mineral fiber MF02-2 is 16:1, the length of aramid pulp fiber is 0.9 to 1.35 mm, the mesh number of antimony sulfide is 250 mesh, the mesh number of alumina is 600 mesh, the mesh number of brass powder Zn20 is 150 mesh, and the mesh number of talcum powder is 800 mesh.
[0029] The present invention also provides a method for preparing a resin-based self-lubricating friction material, which is characterized by comprising the following steps:
[0030] (1) Batching: weigh each component material according to the proportion;
[0031] (2) Mixing: The weighed fiber material is put into a dry mixer and mixed evenly for 0.1 to 0.3 hours; then the remaining material is poured into the mixer and mixed evenly for 0.3 to 0.5 hours;
[0032] (3) Hot pressing: Add the mixed raw materials into the mold for hot pressing at a temperature of 140-180°C and a pressure of 100-350kg / cm 2 , keep time 5~60min;
[0033] (4) Heat treatment: After curing and demoulding, place in an oven and heat from room temperature to 200°C for 20 to 22 hours;
[0034] (5) The semi-finished product after heat treatment is machined according to technical requirements, and then painted and printed to obtain the finished product.
[0035] The invention also provides a brake steel back and a plurality of the above resin-based self-lubricating friction materials arranged on the brake steel back.
[0036] Furthermore, a plurality of strengthening process holes are drilled on the brake steel back.
[0037] Furthermore, the resin-based self-lubricating friction material and the brake steel back are bonded together by curing at high temperature through a structural adhesive, and a chip removal groove is provided on the surface of the resin-based self-lubricating friction material.
[0038] Beneficial effects:
[0039] The friction material of the present invention has the advantages of high mechanical properties, stable friction coefficient and low wear rate, anti-noise and no disk damage. It is an environmentally friendly friction material with a five-year full life cycle and no faults. The friction material design factors fully consider the wind power yaw braking conditions, such as: the friction pad is under a specific pressure of 0.5-5Mpa, the yaw working line speed is 10-20mm per second, and the friction pad is under a specific pressure of 10-28Mpa during anchoring work. The yaw drag damping temperature will not exceed 100°C, and there should be no obvious sharp and harsh yaw noise during yaw damping (Note: 5.216 of NB / T31144-2018 stipulates that the yaw noise requirement is ≤90 decibels), 5.2.12 stipulates that the pad wear rate is ≤0.05mm / km), there should be no signs of disk damage, and normal yaw operation with low noise and no wind turbine tower impact vibration alarm in a 99% humid environment.
[0040] The invention utilizes the advantages of thermoplastic phenolic resin, namely, the plasticity that becomes flexible or plastic when the temperature rises to a certain level, and can form a wear-resistant engineering composite alloy with Teflon as a matrix, and adds the toughening, strengthening and lubricating functions of polyethylene fiber, the lubrication and viscous friction effects of solid lubricants such as antimony sulfide, brass powder and talcum powder, and the application of aramid pulp and mineral fiber reinforcement pore formation and friction increasing agent aluminum oxide, so that boundary friction can be formed between the friction material and the brake disc during wind power yaw operation, and its lubricating transfer film can be highly attached to the brake disc to form an inherent yaw lubrication effect, and has good braking friction performance in a dry and wet environment of 2% to 99%, low yaw operation noise, and no damage to the disc during friction.
[0041] The resin-based self-lubricating friction material of the present invention has the advantages of stable friction coefficient, good lubrication stability and strong wear resistance; it can reduce noise during yaw braking and can perform yaw braking smoothly during operation; on the other hand, it reduces the wear rate of the friction material, greatly prolongs the service life of the friction material, reduces the frequency of replacing the friction plate, and saves the operation and maintenance cost of wind power generation. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a surface electron microscope image of the friction material obtained in Example 1;
[0043] Figure 2 This is a pore analysis diagram of the friction material obtained in Example 1 made on a fully automatic adsorption instrument;
[0044] Figure 3 is a top view of the wind power generation yaw brake pad of embodiment 7;
[0045] Figure 4 The friction vibration spectrum after 5 hours of long-wear test under rated working conditions, where the upper figure is the time domain diagram and the lower figure is the corresponding time-frequency diagram;
[0046] Figure 5 This is the friction vibration spectrum after 5 hours of high humidity long wear test, where the upper figure is the time domain diagram and the lower figure is the corresponding time-frequency diagram;
[0047] Figure 6 This is the friction vibration spectrum after 5 hours of low-roughness long wear test. The upper figure is the time domain diagram, and the lower figure is the corresponding time-frequency diagram. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with specific embodiments.
[0049] The following examples are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention.
[0050] Based on the existing problems of drag friction materials in the yaw system of the existing wind power industry, the present invention starts from the perspective of "research and development - manufacturing - performance testing - application of resin-based self-lubricating friction engineering composite materials", and through experimental research and theoretical analysis, develops excellent resin-based self-lubricating friction materials.
[0051] The raw material information used in the embodiment of the present invention is as follows:
[0052] Mineral fiber MF02-2 Jiangsu Xinguan Braking Technology Co., Ltd.
[0053] Brass powder Zn20 Chengdu Nuclear 857 New Materials Co., Ltd.
[0054] Embodiment 1:
[0055] (1) Ingredients: The raw materials are weighed in order according to the formula, and the weight percentages are as follows: 18% of thermoplastic phenolic resin, 10% of Teflon, 11% of polyethylene fiber, 10% of mineral fiber MF02-2, 9% of aramid pulp, 13% of antimony sulfide, 13% of aluminum oxide, 6% of brass powder Zn20, and 10% of talc. Among them, the mesh number of the thermoplastic phenolic resin is 300 mesh, the mesh number of Teflon is 100 mesh, the length of the polyethylene fiber is 3 to 6 mm, the aspect ratio of the mineral fiber MF02-2 is 16:1, the length of the aramid pulp fiber is 0.9 to 1.35 mm, the mesh number of antimony sulfide is 250 mesh, the mesh number of aluminum oxide is 600 mesh, the mesh number of the brass powder Zn20 is 150 mesh, and the mesh number of the talc is 800 mesh.
[0056] (2) Mixing: The weighed fiber material is put into a dry mixer and mixed evenly for 0.1 to 0.3 hours; then the remaining material is poured into the mixer and mixed evenly for 0.3 to 0.5 hours;
[0057] (3) Hot pressing: Add the mixed raw materials into the mold for hot pressing at a temperature of 155°C, a pressure of 200kg / cm2, and a holding time of 20min;
[0058] (4) Heat treatment: After curing and demoulding, the product was placed in an oven and heated from room temperature to 180°C for 21 hours;
[0059] (5) The semi-finished product after heat treatment is machined according to technical requirements, and then spray-painted and printed to obtain a resin-based self-lubricating friction material named: HW473.
[0060] Example 2: The difference compared with Example 1 is the raw material content ratio, calculated by mass percentage: thermoplastic phenolic resin 16%, Teflon 15%, polyethylene fiber 8%, mineral fiber MF02-2 6%, aramid pulp 5%, antimony sulfide 10%, aluminum oxide 15%, brass powder Zn20 14%, talcum powder 11%.
[0061] Example 3: The difference compared with Example 1 is the raw material content ratio, calculated by mass percentage: thermoplastic phenolic resin 24%, Teflon 12%, polyethylene fiber 6%, mineral fiber MF02-2 10%, aramid pulp 7%, antimony sulfide 8%, aluminum oxide 8%, brass powder Zn20 10%, talcum powder 15%.
[0062] Example 4: The difference compared with Example 1 is the raw material content ratio, calculated by mass percentage: thermoplastic phenolic resin 22%, Teflon 13%, polyethylene fiber 10%, mineral fiber MF02-2 6%, aramid pulp 8%, antimony sulfide 11%, aluminum oxide 11%, brass powder Zn20 6%, talcum powder 13%.
[0063] Example 5: The difference compared with Example 1 is the raw material content ratio, calculated by mass percentage: thermoplastic phenolic resin 25%, Teflon 11%, polyethylene fiber 10%, mineral fiber MF02-2 6%, aramid pulp 8%, antimony sulfide 11%, aluminum oxide 11%, brass powder Zn20 6%, talcum powder 12%.
[0064] Example 6: The difference compared with Example 1 is the raw material content ratio, calculated by the following mass percentage: thermoplastic phenolic resin 26%, Teflon 13%, polyethylene fiber 6%, mineral fiber MF02-2 6%, aramid pulp 8%, antimony sulfide 9%, aluminum oxide 11%, brass powder Zn20 6%, talcum powder 15%.
[0065] Comparative Example 1: The difference compared with Example 1 is the raw material content ratio, calculated by mass percentage: thermoplastic phenolic resin 31%, Teflon 13%, polyethylene fiber 6%, mineral fiber MF02-2 6%, aramid pulp 8%, antimony sulfide 9%, aluminum oxide 17%, brass powder Zn20 6%, talc 4%.
[0066] Comparative Example 2: The difference compared with Example 1 is the raw material content ratio, calculated by mass percentage: thermoplastic phenolic resin 9%, Teflon 20%, polyethylene fiber 13%, mineral fiber MF02-2 6%, aramid pulp 8%, antimony sulfide 9%, aluminum oxide 17%, brass powder Zn20 6%, talcum powder 12%.
[0067] Example 7: Figure 3 As shown, this embodiment provides a wind power generation yaw brake pad, including a brake steel back 1 and a resin-based self-lubricating friction material 2 (referred to as friction material) arranged on the brake steel back 1.
[0068] The friction material and the brake steel back 1 are bonded together by structural adhesive that is cured at high temperature. To increase the bonding strength between the two materials, 20 reinforcing process holes with a diameter of 20 mm and a number of 20 holes are drilled on the brake steel back 1 to increase the bonding strength between the friction material and the brake steel back.
[0069] The surface of the friction material is provided with a chip groove 21, which can dissipate heat, remove chips and reduce friction noise.
[0070] 1. Friction and noise performance test:
[0071] The test is carried out on a wind turbine yaw test bench according to the requirements of the wind turbine yaw braking working conditions. During the test, the materials prepared in the above embodiments 1-6 are respectively made into brake pads and installed on the SB540-A02 yaw brake. A yaw drag dynamic friction test with a stroke of 10,000 meters is carried out with a pipeline pressure of 2.5 MPa and a sliding drag speed of 10 mm per second. Then, when the stroke reaches 10,000 meters, a static friction drag test is carried out at a pipeline pressure of 16 MPa.
[0072] According to the technical requirements, the friction material is first tested for thickness, and then installed in the brake on the wind power yaw test bench. According to the rated working conditions of the brake dragging, a 10,000-meter yaw dragging test is first performed with a pipeline pressure of 2.5MPa and a dragging speed of 10mm / s. When the stroke reaches 10,000 meters, a static friction coefficient test under 16MPa is then performed. After the test, the friction material is removed and the material thickness after the friction material is worn is measured to obtain the wear rate of the friction material. The test results are shown in Table 1:
[0073] Table 1 Comparison of friction and noise
[0074]
[0075]
[0076] After the test, it was observed that the friction materials of Examples 1-6 did not show abnormal phenomena such as crushing, falling off, and edge collapse. The brake discs of the dual parts had no scratches and a smooth surface, and the dual parts did not adhere to other friction dust and iron powder. The test results show that the friction coefficient, wear rate, noise and other indicators of the friction materials prepared in Examples 1-6 under rated conditions all meet the relevant provisions of the clauses (5.2.16., 6.4.2, 5.2.6, 5.2.9) of "NB / T31144-2018".
[0077] 2. Physical performance test see Table 2:
[0078] Table 2: Comparison of physical performance tests
[0079]
[0080]
[0081] Figure 1 is a surface electron microscope image of the friction material obtained in Example 1; Figure 1 It can be seen that the aramid pulp is well distributed in the friction material in a dendrite-like manner, and is arranged in a disordered manner and fully bonded with the thermoplastic phenolic resin to form a mesh-like porous material.
[0082] Figure 2 This is a pore analysis diagram of the friction material obtained in Example 1 made on a fully automatic adsorption instrument; the pore size distribution is between 1.682 and 34.482 nm, and most of the pore size is concentrated at 2.382 nm, belonging to a porous-mesoporous friction material.
[0083] The base material of the friction material of the present invention is a porous material composed of thermoplastic phenolic resin, high-toughness polyethylene fiber, aramid pulp and mineral fiber. Therefore, during yaw operation, it can reduce the mutual transmission of sound waves by the sound wave frequency generated by friction vibration through the fiber-enhanced self-strength, toughness and porous internal sound insulation interference and absorption of the sound wave frequency, so as to play a shock-absorbing role, so that the yaw friction vibration harmonics will not be excited and resonated with the natural frequency of the wind turbine tower during the transmission process, thereby reducing the vibration noise during the yaw process. Secondly, a low-wear rate self-lubricating friction base is composed of Teflon, brass powder, talcum powder and polyethylene fiber. The self-lubricating transfer film formed during the yaw boundary friction process can play a self-lubricating role on the friction surface, so that the friction force of the friction surface can be evenly distributed on the friction surface without generating large friction vibration harmonics. Due to the low friction wear rate, the stick-slip effect caused by the friction enamel layer is avoided.
[0084] 3. Friction and wear test:
[0085] The test was carried out on the laboratory UMT-5 multifunctional friction and wear testing machine:
[0086] Table 3 Friction vibration noise test conditions
[0087]
[0088] Friction vibration noise analysis:
[0089] The brake pad made of the friction material of Example 1 was tested according to Test No. 1 in Table 3. The friction vibration spectrum after the rated working condition long wear test for 5 hours is shown in FIG. Figure 4 ,in, Figure 4 The upper figure is the time domain diagram, and the lower figure is the time-frequency diagram. The duration of each analysis is 2s. The time-frequency diagram is obtained by sliding the small window Fourier transform calculation on the time domain diagram data. It can be clearly seen from the time-frequency diagram that within the 2s analysis interval, the vibration can be divided into a stage of 0.25s, and there is a clear boundary between each stage. This boundary is caused by the reciprocating frequency of 2Hz in the reciprocating test. The duration of each stroke is 0.25s, which is consistent with the vibration acceleration signal. The vibration acceleration amplitude and frequency of the rated working condition long wear test are analyzed. It can be seen that the amplitude remains basically constant throughout the test stage. At the same time, there is no obvious vibration main frequency peak in the range of 0-4000Hz.
[0090] The brake pad made of the friction material of Example 1 was tested according to Test No. 2 in Table 3. The friction vibration spectrum after the high humidity long wear test for 5 hours is shown in FIG. Figure 5 ,in, Figure 5 The upper figure in the figure is the time domain diagram, and the lower figure is the corresponding time-frequency diagram. Figure 5 It can be seen that the amplitude remains basically constant throughout the test phase and is similar to the long-term wear test results under rated conditions. At the same time, there is no obvious peak value of the main vibration frequency in the range of 0-4000Hz.
[0091] The brake pad made of the friction material of Example 1 was tested according to Test No. 3 in Table 3. The friction vibration spectrum after the low roughness long wear test for 5 hours is shown in FIG. Figure 6 ,in, Figure 6 The upper figure is the time domain diagram, and the lower figure is the time-frequency diagram. Figure 6 It can be seen that its amplitude remains basically constant throughout the test phase, and no obvious vibration main frequency peak appears in the range of 0-4000Hz.
[0092] Comparison between HW473 installed in wind farm base and other manufacturers' products:
[0093] Table 4: Operation data record of vibration sensor of wind turbine yaw unit in a wind farm 1
[0094]
[0095] Table 5: Operation data record of vibration sensor of wind turbine yaw unit in the above wind farm 2
[0096]
[0097] Table 6: Operation data record of the vibration sensor on the top of the wind turbine yaw unit in a wind farm 3
[0098]
[0099] From the operating results in Tables 4 to 6, it can be seen that HW473 has no anchor slip phenomenon and has the characteristics of large friction coefficient, low noise in yaw movement, low wear without damaging the disc, and stable yaw friction.
Claims
1. Resin-based self-lubricating friction material, characterized in that: By weight percentage, it includes the following components: Thermoplastic phenolic resin 10-30%; Teflon 10-15%; Polyethylene fiber 6-12%; Mineral fiber MF02-2 5-10%; Aramid pulp 5-10%; Antimony sulfide 4-15%; Alumina 10-15%; Brass powder Zn20 5~15%; Talc 5-15%.
2. The resin-based self-lubricating friction material according to claim 1, characterized in that: The friction material comprises the following components by weight percentage: Thermoplastic phenolic resin 18%; Teflon 10%; Polyethylene fiber 11%; Mineral fiber MF02-2 10%; Aramid pulp 9%; Antimony sulfide 13%; Alumina 13%; Brass powder Zn20 6%; Talc 10%.
3. The resin-based self-lubricating friction material according to claim 1, characterized in that: The mesh number of thermoplastic phenolic resin is 200-400 mesh, the mesh number of Teflon is 40-200 mesh, the length of polyethylene fiber is 3-6 mm, the aspect ratio of mineral fiber MF02-2 is 8:1-18:1, the length of aramid pulp fiber is 0.9-1.35 mm, the mesh number of antimony sulfide is 200-320 mesh, the mesh number of alumina is 500-600 mesh, the mesh number of brass powder Zn20 is 150-200 mesh, and the mesh number of talc is 600-800 mesh.
4. The resin-based self-lubricating friction material according to claim 1, characterized in that: The mesh number of thermoplastic phenolic resin is 300 mesh, the mesh number of Teflon is 100 mesh, the length of polyethylene fiber is 3-6 mm, the aspect ratio of mineral fiber MF02-2 is 16:1, the length of aramid pulp fiber is 0.9-1.35 mm, the mesh number of antimony sulfide is 250 mesh, the mesh number of alumina is 600 mesh, the mesh number of brass powder Zn20 is 150 mesh, and the mesh number of talcum powder is 800 mesh.
5. A method for preparing a resin-based self-lubricating friction material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Batching: weigh each component material according to the proportion; (2) Mixing: The weighed fiber material is put into a dry mixer and mixed evenly for 0.1 to 0.3 hours; then the remaining material is poured into the mixer and mixed evenly for 0.3 to 0.5 hours; (3) Hot pressing: Add the mixed raw materials into the mold for hot pressing at a temperature of 150-160°C and a pressure of 150-250kg / cm 2 , keep for 10 to 30 minutes; (4) Heat treatment: After curing and demoulding, place in an oven and heat from room temperature to 180°C for 20 to 22 hours; (5) The semi-finished product after heat treatment is machined according to technical requirements, and then painted and printed to obtain the finished product.
6. A wind power generation yaw brake pad, characterized in that: The invention comprises a brake steel back and a plurality of resin-based self-lubricating friction materials as claimed in any one of claims 1 to 4 arranged on the brake steel back.
7. A wind power generation yaw brake pad according to claim 6, characterized in that: The brake steel back is drilled with multiple strengthening holes.
8. The wind power generation yaw brake pad according to claim 6, characterized in that: The resin-based self-lubricating friction material and the brake steel back are bonded together by curing at high temperature through a structural adhesive, and a chip removal groove is arranged on the surface of the resin-based self-lubricating friction material.